M management - Bateman, Thomas S.; Snell, Scott A.; Konopaske, Robert (McGraw-Hill Education, 2020)
"Overall, the seventh edition of M: Management is more streamlined and reader-friendly, with current content and a layout that is visually appealing to today's college learner. The endnotes also have been updated and expanded"--Provided by publisher.